Differences Between Omnivores and Vegetarians in Personality Profiles, Values, and Empathy: A Systematic Review - Holler, Sophie; Cramer, Holger; Liebscher, Daniela; Jeitler, Michael; Schumann, Dania; Murthy, Vijayendra; Michalsen, Andreas; Kessler, Christian S. (Frontiers in Psychology, 2021)
Numerous medical studies have documented vegetarian diets having various health benefits. Studies also compare vegetarians with other dietary groups from a socio-psychological perspective. The aim of this review is to investigate differences between vegetarians and omnivores in terms of personality profiles, values and empathy skills. A literature search was conducted across three electronic databases. Non-randomized, observational, cross-sectional and cohort studies were eligible. Outcomes provided information about differences between the above mentioned dietary groups regarding their personality profiles, values, and empathy skills. A shortened version of the Newcastle-Ottawa Scale was used to assess the risk of bias for the included studies. Of the 1,755 different studies found, 14 (total n=6,368) were ultimately included. These studies indicate that vegetarians significantly differ from omnivores in their personality, values and ability to be empathetic. Omnivorism is associated with greater right-wing authoritarianism, increased orientation towards social dominance and a stronger tendency to be prejudiced. Vegetarianism is associated with greater openness and empathy. Vegetarians’ values are based more on hedonism, universalism, stimulation and self-direction, whereas omnivores’ values are based more on the idea of power. In order to answer a narrowly defined and clear question, issues such as animal ethics, animal rights and environmental protection are not considered in this review. The findings of this review, showing marked differences in personality correlating to the choice of diet and the increasing influence of plant based diets on the global level, indicate that further studies on the subject of vegetarianism are warranted.